Sistematización de experiencias del: "Grupo Pro Agua sin Arsénico" en la problemática de contaminación del agua con arsénico en la parroquia de Tumbaco. - García Salazar, Ana Lucía (2012)
In 2004 it is known that in the parish of Tumbaco, of the drinking water distributed by the Municipal Water and Sewer Public Quito, was contaminated with arsenic. From his knowledge a group begins to meet people to socialize the subject, producing great excitement for this discovery. This group of villagers decided to form a front Tumbaco control through the creation of the Committee for arsenic-free water "CPASA". Legally constituted takes legal action to the municipal EMAAP-Q by hiding information about the problems and neglect by providing contaminated water to an entire population.